Items analysis of the Frailty Index (FI-35): Insight in the contribution of each item to the level of frailty. - Xiaohong Zhang (Public Library of Science (PLoS), 2021)
Background The FI-35 is a valid multidimensional Chinese frailty assessment instrument. Like other scales, functional measures rely on the information the total score provides. Our research aimed to analyze the contribution of each item. Methods Descriptive statistics were used to summarize the sample characteristics. The expected item score (EIS) was used to determine how the items contribute to the generic measure of frailty. Results This study showed that most of the EIS curves increased across the entire range of frailty levels, and most of the items discriminate relatively well over the entire frailty range. Items differentially contributed to the total frailty score and differentially discriminated between frailty levels. Conclusions Although nearly all items monotonically increased with frailty levels, there were large differences between items in their ability to differentiate between persons being either weakly, moderately or highly frail.